Formação Superior em Educação Física no Brasil : um estudo de caso - Vieira Dias, Leon Ramyssés (Educación Física y Ciencia.)
The Higher Formation in Physical Education has been increasingly discussed by researchers in the field. Currently, the course is divided into undergraduate and baccalaureate degrees, regulated by Regulations CNE / CP 01/02 and CNE / CES 07/04, respectively. A new regulation (CNE / CES, 06/2018), criticized by Physical Education researchers, among other modifications, makes it possible for Higher Education Institutions to offer two formations in a single curriculum. From this situation, this article aims to compare and analyze the Projects-Political-Pedagogical of a Federal University that offers, in different curricula, undergraduate and baccalaureate. From a broad data collection, a case study methodology was used to portray the possible approximations and the possible distancing between undergraduate and baccalaureate at Federal Universities. In addition, the data were also treated qualitatively inspired by the educational principle of Antonio Gramsci. As a result, it may be noted that there is a wide range of disciplines common to both courses, as well as a formation proposal, but they are offered separately. Thus, we concluded that the offer of the Physical Education course can be reconceptualized and rethought from the new Curricular Guidelines.